The Functional Interrelation of Central Pillars inEnclosure D at Portasar (G¨obekli Tepe) - Malkhasyan, H. A.
This study aims to reinterpret the spatial relationship between the central Pillars 18 and 31 of Enclosure D at Portasar (G¨obekli Tepe), considering it as a potential practical instrument for determining the summer solstice and equinoxes. A shadow-tracking simulation was conducted using positional data from the Pillars, architectural plans, and the Stellarium 24 astronomical software. The mutual positions of the Pillars’ shadows were examined during the four key dates of the year—winter and summer solstices, and the vernal and autumn equinoxes, at sunrise and sunset. The results show that only at sunrise on the summer solstice do the shadows align in such a way that a light-filled gap appears between the Pillars, directed southwest. During the equinoxes, the shadows produce a “gating” effect—opening at sunrise and close at sunset. The “H” and “I” symbols carved on Pillar 18 (as well as on other Pillars at the site) may correspond to the horizontal and vertical trajectories of the observed shadows. Furthermore, a visual correlation is observed between the imagery on a carved bone spatula and the sunrise during the summer solstice. These findings suggest a potential shadow-based calendrical application for the Pillars.
Keywords: Astrophysics